Knowledge and Attitude toward Deprofessionalization among Dental Health Professionals – A Questionnaire-based Survey - Princy Annuncia Elias; Nanda Balan Iyenkani; Zoha Abdullah; N. Indira; Arun Kumar Sundaragopal; Rajkumar Chakkarapani (Journal of Indian Association of Public Health Dentistry)
Background: Deprofessionalization is a process where less-qualified individuals are used to perform work which is done by appropriately qualified individuals. Inequity in the distribution of healthcare services leads to the disparity in dentists in urban and rural areas leading to increased unmet dental needs. To tackle these, community health workers (CHWs) can be trained by the dentists to provide oral health education. This can be achieved by assessing dentists’ knowledge and attitude toward deprofessionalization and their willingness to train CHWs. Methodology: The present survey was conducted among 300 dental health professionals. Online questionnaire link was constructed using the Google survey tool of Gmail comprising 13 questions. For descriptive and frequency statistics, SPSS 27 was used. Results: About 94.1% of the study population thought that it is important for dentists to be posted in government health centers. About 64.4% thought that the provision of basic oral health services by trained CHWs would be beneficial. About 66.3% supported training CHWs in providing basic oral health care. Conclusion: Training CHWs will improve their ability to motivate patients in rural India to utilize oral healthcare services.